2015
DOI: 10.1371/journal.pone.0123394
|View full text |Cite|
|
Sign up to set email alerts
|

Threatened Caribbean Coral Is Able to Mitigate the Adverse Effects of Ocean Acidification on Calcification by Increasing Feeding Rate

Abstract: Global climate change threatens coral growth and reef ecosystem health via ocean warming and ocean acidification (OA). Whereas the negative impacts of these stressors are increasingly well-documented, studies identifying pathways to resilience are still poorly understood. Heterotrophy has been shown to help corals experiencing decreases in growth due to either thermal or OA stress; however, the mechanism by which it mitigates these decreases remains unclear. This study tested the ability of coral heterotrophy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
108
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(118 citation statements)
references
References 49 publications
7
108
2
1
Order By: Relevance
“…Nevertheless, when photosynthesis was reduced in both fed and unfed corals at high temperature, calcification was also reduced by 61–65% compared to control temperature at day 28, and by 46–53% at day 56. These results suggest that heterotrophic feeding does not alter the sensitivity of corals to heat stress, as previously observed in corals under acidification stress63646566. Our observation is also in contrast to other studies demonstrating that supply of inorganic nutrients can reduce calcification sensitivity to both heat stress and to ocean acidification66676869.…”
Section: Discussionsupporting
confidence: 72%
“…Nevertheless, when photosynthesis was reduced in both fed and unfed corals at high temperature, calcification was also reduced by 61–65% compared to control temperature at day 28, and by 46–53% at day 56. These results suggest that heterotrophic feeding does not alter the sensitivity of corals to heat stress, as previously observed in corals under acidification stress63646566. Our observation is also in contrast to other studies demonstrating that supply of inorganic nutrients can reduce calcification sensitivity to both heat stress and to ocean acidification66676869.…”
Section: Discussionsupporting
confidence: 72%
“…Thus, our finding of enhanced calcification during periods of increased heterotrophy runs counter to some modeling and field-based studies (10,19). However, numerous experiments have shown that if corals, the dominant reef calcifiers, are well fed (such as by zooplankton) or have nutritionally replete diets, they will have greater rates of both tissue and skeletal growth (20)(21)(22)(23)(24). Some results have even demonstrated that corals may be able to counteract reduced rates of calcification resulting from OA by increasing feeding rates (23).…”
Section: Resultscontrasting
confidence: 58%
“…Given the experimental evidence linking increased heterotrophy to higher calcification rates in corals (20)(21)(22)(23)(24) and the statistical significance of our cross-correlation analysis, we hypothesize that lateral advection of offshore blooms as well as nutrient upwelling, both of which were exacerbated during the winters of 2010 and 2011, possibly due to the NAO state, provided external pulses of nutrition to the reef. These pulses of nutrition enabled short-term shifts in reef NEC and NEP toward increasing calcification and heterotrophy, respectively, and it was these biogeochemical shifts that ultimately caused the observed changes in seawater pH and Ω aragonite (Fig.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Pandolfi et al () pointed out that, although lab, mesocosm, and field studies indicate that the impact of acidification is consistently negative (Kroeker et al ), the relationship with saturation state is highly variable and often nonlinear. Sensitivity to decreases in pH seems to be reduced when corals are given weeks, rather than days, to acclimate (Marubini et al ; Reynaud et al ; Ries et al ) when they have abundant food (Ries et al ; Edmunds ; Towle et al ), or are supplied with high levels of inorganic nutrients (Langdon and Atkinson ; Ezzat et al ). This broad range of variability in sensitivity to pH may partly be explained by differences in experimental methodology, but it is likely that there are real differences between species.…”
mentioning
confidence: 99%